Experimental study of the mechanisms of steam reactivation of unreacted calcium-based sorbent for Flue Gas Desulphurisation. (22nd August 2008) - Wang, Aijun; Tan, Zhongchao; Qi, Haiying; Xu, Xuchang
This paper reports an experimental investigation of the mechanisms of steam reactivation of spent sorbent for flue gas desulphurisation. Sulphated lime samples were reactivated by using steam to increase the conversion rate of sorbent for flue gas desulphurisation. Samples were characterised using mercury porosimeter, XRD, and SEM. Reactivation temperatures were in the range of 200-800°C. Retention times were 5, 10, and 20 min. For the conditions within this work, it was found that sorbent particles broke down when reactivated at 200°C, and migration of trapped CaO outward was the main mechanism when reactivation temperature was greater than 300°C. [Received: April 9, 2007; Accepted: October 2, 2007]